2018
DOI: 10.1080/1359432x.2018.1443914
|View full text |Cite
|
Sign up to set email alerts
|

The future of workplace commitment: key questions and directions

Abstract: This position paper presents the state-of-the art of the field of workplace commitment. Yet, for workplace commitment to stay relevant, it is necessary to look beyond current practice and to extrapolate trends to envision what will be needed in future research. Therefore, the aim of this paper is twofold, first, to consolidate our current understanding of workplace commitment in contemporary work settings and, second, to look into the future by identifying and discussing avenues for future research. Representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
30

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(136 citation statements)
references
References 128 publications
1
105
0
30
Order By: Relevance
“…The findings allow us to affirm that the ties show distinct antecedent and subsequent factors, corroborating the most recent theoretical perspectives (Bastos & Aguiar, 2015;Pinho et al, 2015b;Rodrigues & Bastos, 2015;Rodrigues et al, 2019; 255 255 2015). In strengthening the evidence that they are different ties, with equally distinct antecedents and consequences, we sustain the need to understand how multiple ties configure and work in an integrated form, i.e., how the multiples commitments are substituted, conflictual, complementary and work in synergy with other ties (Rossenberg et al, 2018). The evidence found strengthens the outlining of the concept of organisational commitment within its affective base, overcoming the threecomponent model by Meyer and Allen (1991).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The findings allow us to affirm that the ties show distinct antecedent and subsequent factors, corroborating the most recent theoretical perspectives (Bastos & Aguiar, 2015;Pinho et al, 2015b;Rodrigues & Bastos, 2015;Rodrigues et al, 2019; 255 255 2015). In strengthening the evidence that they are different ties, with equally distinct antecedents and consequences, we sustain the need to understand how multiple ties configure and work in an integrated form, i.e., how the multiples commitments are substituted, conflictual, complementary and work in synergy with other ties (Rossenberg et al, 2018). The evidence found strengthens the outlining of the concept of organisational commitment within its affective base, overcoming the threecomponent model by Meyer and Allen (1991).…”
supporting
confidence: 54%
“…In the debate on commitment dimensionality (Allen, 2016;Klein & Park, 2016) and the emerging discussion on how multiple commitments consolidate and coexist (Rossenberg et al, 2018), in different organisational contexts (Wasti et al, 2016), arises the proposition that the tie of affective nature strongly differs from instrumental and normative ties. Along this line of thinking, the studies of Rodrigues (2009) and Silva (2009) question whether the notion of commitment suits the permanence of the individual for necessity or obligation.…”
Section: Organisational Ties: Commitment Entrenchment and Consentmentioning
confidence: 99%
“…Previous research has shown that employees hold multiple commitments and bonds in their career (van Rossenberg et al, 2018). Thus, COC should be examined in connection to, and distinguished from, closely related commitments and bonds.…”
Section: Study 1: Examining Coc's Distinctiveness and Ability To Predmentioning
confidence: 99%
“…Beforehand, it is important to mention that several commitment models have been proposed over the years (e.g., Cooper-Hakim & Viswesvaran, 2005;Klein, Molloy, & Brinsfield, 2012;Meyer & Allen, 1991;Meyer & Herscovitch, 2001;Morrow, 1993). Among them, Meyer and Allen's (1991;see also Meyer & Herscovitch, 2001) threecomponent model is most widely studied (van Rossenberg et al, 2018). This model distinguishes among three components, that is, affective, normative, and continuance (which subsumes perceived sacrifice and few alternatives; Taing, Granger, Groff, Jackson, & Johnson, 2011) and has been applied to various targets such as the organization and the supervisor.…”
Section: Study 1: Examining Coc's Distinctiveness and Ability To Predmentioning
confidence: 99%
“…We use a lens of attachment to explore microworkers' perceptions of this employment relationship. Our theorisation draws from frameworks which view attachment as a dynamic and socially constructed phenomenon especially appropriate for understanding temporary and virtual working, such as online gig work (van Rossenberg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%